The Genetic Architecture of Barley Plant Stature - Alqudah, Ahmad M.; Koppolu, Ravi; Wolde, Gizaw M.; Graner, Andreas; Schnurbusch, Thorsten (Frontiers in Genetics, 2016)
Plant stature in temperate cereals is predominantly controlled by tillering and plant height as complex agronomic traits, representing important determinants of grain yield. This study was designed to reveal the genetic basis of tillering at five developmental stages and plant height at harvest in 218 worldwide spring barley (Hordeum vulgare L.) accessions under greenhouse conditions. The accessions were structured based on row-type classes [two- versus six-rowed] and photoperiod response [(photoperiod-sensitive (Ppd-H1) versus reduced photoperiod sensitivity (ppd-H1)]. Phenotypic analyses of both factors revealed profound between group effects on tiller development. To further verify the row-type effect on plant height and tiller number, Six-rowed spike 1 (vrs1) mutants and their two-rowed progenitors were examined for tiller number per plant and plant height. Here, wild-type (Vrs1) plants were significantly taller and had more tillers than mutants suggesting a negative pleiotropic effect of this row-type locus on both traits. Our genome-wide association scans further revealed highly significant associations, thereby establishing a link between the genetic control of row-type, heading time, tillering and plant height. We further show that associations for tillering and plant height are co-localized with chromosomal segments harboring known plant stature-related phytohormone and sugar-related genes. This work demonstrates the feasibility of the GWAS approach for identifying putative candidate genes for improving plant architecture.